The effect of sole reflexology on severity of fatigue in pregnant women - Pourghaznein T; Ghafari F (Tehran University of Medical Sciences, 2006)
Background & Aim: Fatigue is a significant problem during pregnancy that has rarely been studied, and may increase the number of caesarean deliveries and preterm births. Reflexology can be utilized for decrease of fatigue. Therefore this study was aimed to identify the effect of sole reflexology on pregnant women's fatigue severity. Methods & Materials: This research was a clinical trail study using a pre-post test design. The subjects consisted of 74 pregnant women referred to treatment health centers of Ramsar city, with 36 and 38 cases in the test and control group respectively. Sole reflexology was preformed for 30 minutes, twice a week through five weeks, in the test group. To evaluate the effect of sole reflexology, the score of fatigue was measured before and after the experiment in both groups. The instruments used included: The sample selection form, demographic data form and fatigue severity questionnaire. The collected date was analyzed by chi-square, t-test, and paired t-test Pearson correlation coefficients. Results: There was a statistically significant decrease in fatigue in the test group compared to the control group, after reflexology. (p=0.0001). In addition there was significant negative relationship between score of fatigue and social support (r=-0.46, p=0.002) and also score of fatigue in persons that received ferrous sulfate significantly lower than others. (p<0.000). Conclusion: According to the results of this study It is suggested that sole reflexology might have beneficial effects on reducing fatigue in pregnant women, and can be recommended as a nursing intervention program for this persons.